The Link Between: Culture and Sustainability in Municipal Planning - Stanborough, Maria (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
This article explores the link between culture and sustainability from a municipal planning perspective based on experiences at the City of Kelowna. It examines how culture has been integrated within municipal planning, and how sustainability is being woven within cultural planning practices. The process has just recently begun at the City of Kelowna but already the municipality has experienced a number of practical learning opportunities. The most pertinent examples show that culture is an integral component of long-term community sustainability.